India and Southeast Asia strategic convergence in the twenty-first century - Nirmala Devi, T.; Subramanyam Raju, A. (Institute of Southeast Asian Studies Manohar, 2012)
Southeast Asia and India are geographically contiguous. They share common histories and colonial experiences. During their freedom struggle and later, Southeast Asian countries expected India to support them not only politically but also economically for their development. However, due to various reasons including its preoccupation with domestic problems arising from partition, an inward-looking economy, the war with China and in particular the Cold War divisions, India could not take an interest in the region. Some of the Southeast Asian countries did not support India when it had conflicts with China and Pakistan, which made New Delhi keep its distance from the region. Though efforts were made to evaluate the policy course, some of the developments made both entities drift away from each other. Disintegration of the Soviet Union and India's relationship with the U.S. in the post-Cold War period had a positive effect on India-Southeast Asian relations. Both entities recognize the importance of each other. The Southeast Asian countries have begun to see India as an economic power and have now become a major player in foreign direct investment stakes in India. India is active in setting up regional economic and development groupings like BIMSTEC and the Mekong Ganga project. It also aims at developing land connectivity with the region through Myanmar and Thailand. Both India and Southeast Asian countries, as this timely volume shows, now increasingly view each other in a more constructive way. The volume focuses on various issues pertaining to relations between India and Southeast Asia.